Unijne środki handlowe w regulacji rynku rybnego - Marciniak, Mirosława (Union Trade Instruments Used in Regulation of Fish Market, 2005)
The paper presents selected union trade instruments used in international trade (tariff quotas, ceiling). They are very important for Polish fish industry, which is based on import of fish products. An access to cheaper fish sources makes possibilities for the development of fish industry and increases competition on the common market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 75-79